Integrating EQUIP competency-based training into a university curriculum: a qualitative inquiry with students and faculty at Makerere University in Uganda - Ndeezi, Morris; Pedersen, Gloria A.; Alipanga, Benjamin; Luberenga, Ibrahim; Kohrt, Brandon A.; Kasujja, Roscoe (Frontiers in Education, 2024)
Abstract Introduction: Competency-based training has gained prominence in clinical psychology education, emphasizing practical skills acquisition. The EQUIP competency-based approach, recognized for its effectiveness in in-service training, raises questions about its feasibility and utility in pre-service education. Methods: Faculty and supervisors were trained in and applied EQUIP competency-based assessment and techniques with current graduate students. A cohort comprising 15 graduate students, 12 faculty members, and supervisors from Butabika National Referral Mental Health and Teaching Hospital participated in focus group discussion and key informant interviews. Qualitative data was collected from 1st August 2022 to 4th August 2022. Thematic analysis identified three central themes. Findings: The first theme reveals participants' recognition of EQUIP's feasibility in standardizing competence levels and addressing curriculum gaps. An extended training period, approximately 15 hours, was identified as crucial to enhance educators' and supervisors' confidence in implementing the approach. The second theme emphasizes the pivotal role of role-play in competency-based training, transforming initial apprehension into constructive learning. Lastly, feedback emerged as a crucial component, with participants highlighting its role in fostering self-assuredness and refining skills. Conclusions: The study emphasizes the importance of robust training in competency-based methodologies. The EQUIP approach's potential in clinical psychology education is evidenced by its alignment with research outcomes. Beyond this, the study advocates for longitudinal research to assess sustained engagement with EQUIP resources and their long-term impact. This research not only advances the discourse on competency-based training but also sets the stage for continuous improvements in clinical psychology education.